A bacterial kinase phosphorylates OSK1 to suppress stomatal immunity in rice - Shanzhi Wang (Nature Portfolio, 2021)
XopC2 effectors are present in many plant bacterial pathogens. Here the authors show that XopC2 has kinase activity and enhances disease susceptibility by phosphorylating the OSK1 protein, which increases its interaction with the jasmonate receptor COI1b to promote JA signaling and stomatal opening.